AFORS-HET-based simulation and optimization of ITO/p-rGO/n-cSi heterojunction solar cell for high-efficiency scalable photovoltaics - Chandra Kamal Borah; Lakhi Nath Borah (Next Materials)
This study investigated a heterojunction solar cell incorporating reduced graphene oxide (p-rGO) as the emitter layer on n-type crystalline silicon (n-cSi), where indium tin oxide (ITO) was used as the transparent front contact. Device simulations were performed via AFORS-HET software to evaluate and optimize the photovoltaic performance. The key material parameters of p-rGO, i.e., the doping concentration, bandgap, electron affinity, and dielectric constant, were systematically varied to analyze their effects on device behavior. An initial efficiency of 6.3 % was obtained using a bilayer rGO configuration. Further optimization of the n-cSi absorber layer, particularly in terms of the doping concentration and electronic properties, increased the power conversion efficiency to 14.55 %. The cell demonstrated a strong spectral response in the visible region, with high internal and external quantum efficiencies near 400 nm, indicating efficient charge carrier generation and collection. The sheet resistance and built-in potential were 3.3 Ω/cm² and 0.25 eV, respectively, reflecting favorable interfacial characteristics. These findings underscore the potential of rGO as a cost-effective and scalable alternative to traditional emitter materials in silicon-based photovoltaic devices. This work provides a theoretical framework that may guide future experimental efforts aimed at developing high-efficiency, carbon-based solar cell technologies.